2015
DOI: 10.1186/s40634-015-0021-5
|View full text |Cite
|
Sign up to set email alerts
|

Histological characteristics of ligament healing after bio-enhanced repair of the transected goat ACL

Abstract: BackgroundRecently, healing of a ruptured anterior cruciate ligament (ACL) is reconsidered. In a previous study, we have shown that the transected ACL can heal after treatment with the triple X locking suture alone or combined with small intestine submucosa (SIS). The first research question of this study was whether the healing ACLs in both groups show histological characteristics that are typical for ligament healing. Secondly, did the combined treatment with SIS lead to improved histological healing, in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Histologic features of the ACL healing response after experimental transection, followed or not by surgery, are only scarcely described in the literature. Collagen fibers mild disorganization, decreased presence of voids and fat vacuoles, spindle-shaped fibroblasts, and neovascularization (assessed in the present study, respectively, through cystic changes, chondroid metaplasia, and inflammation criteria) were previously identified as healing response features in transected ACLs, 12 weeks after suture alone or combined with augmentation using small intestine submucosa [56]. Interestingly, neovascularization is sometimes considered as a healing, or as a degenerative pattern of ACL.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Histologic features of the ACL healing response after experimental transection, followed or not by surgery, are only scarcely described in the literature. Collagen fibers mild disorganization, decreased presence of voids and fat vacuoles, spindle-shaped fibroblasts, and neovascularization (assessed in the present study, respectively, through cystic changes, chondroid metaplasia, and inflammation criteria) were previously identified as healing response features in transected ACLs, 12 weeks after suture alone or combined with augmentation using small intestine submucosa [56]. Interestingly, neovascularization is sometimes considered as a healing, or as a degenerative pattern of ACL.…”
Section: Discussionsupporting
confidence: 50%
“…Some authors allocated the absence of spontaneous ACL healing to the gap formed between the ACL ends and subsequent interposition of synovial fluid, which impair the possibility of a guided regeneration process [5]. Indeed, healing of ACL remnants has been previously observed on histology 12 weeks after surgery in a goat model of mid-substance transection followed by locking suture, alone or combined with small intestine submucosa [56]. Some authors suggested spontaneous healing capacities of the ruptured ACL when in contact with its surrounding tissues [57].…”
Section: Discussionmentioning
confidence: 99%
“…In tendon, the resident cells, which consist of tenoblasts and [192] with permission from Springer Nature and Ref. [193]) tenocytes accounted for 90-95% of the cellular components, the rest are chondrocytes, synovial cells and vascular cells [27]. In ligament, the resident cells are made up of ligamentocytes that represent only a small percentage of the total ligament volume [25].…”
Section: Tendon/ligament Structure and Functionmentioning
confidence: 99%
“…4,6,10,13,25,27,31 Nevertheless, only few studies have reported the physiological and biomechanical alterations of the collateral ligaments within the knee joint following ACLT. 28,35,37,54 Experimental and numerical studies have investigated collateral ligament mechanics following ACLT. For instance, large stresses were measured on the collateral ligaments of human cadaveric knees under weight-bearing conditions after ACLT.…”
Section: Introductionmentioning
confidence: 99%